The Atmospheric Circulation and Arctic Meteorology - Hare, F. Kenneth (ARCTIC, 1969)
Reviews advances since 1954 in knowledge of tropospheric and stratospheric circulations: in the former, the nature, distribution and effects of an arctic jet stream and arctic front; and in the stratosphere and mesosphere, the startling discovery of a powerful stratospheric ridge over or west of Alaska (No 63579), which deforms the stratospheric polar-night westerlies up to at least 55 km.